(3EHOGd GdCOhjg GdeaQOIs - (3HOjZhQSs
(3ChdgG (B:s
(3gPG cJGH jOjahQS GdajdSha ai EHOGd GdCOhjI GdeaQOI hGdCTLGQ hGdUehZ hGdWjb s
(3BNQgG (B:s
(3GdPi bGd dg GdTjN , HOdg CQHY hQbGJ RjO GdHMQ Je cJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B6 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CjGUhajG (B(3572(3)) s
Keywords: (3GdWHs